Was Nigeria’s offering of Asylum status to President Charles Taylor of Liberia a diplomatic blunder? A foreign policy case review - Ngara, Christopher Ochanja (Universiti Utara Malaysia Press, 2022)
This paper critically examines the appropriateness or otherwise of the granting of asylum status to former Liberian President, Charles Taylor by the Nigerian government on August 11, 2003. The paper argues that the granting of asylum status to Taylor was consistent with Nigeria’s Afrocentric foreign policy and traditional “big brother” role in Africa. The objective of the asylum was to end the 14-year-old-conflict and return peace and stability to Liberia. However, after the asylum was granted to Mr. Taylor, Nigeria came under serious international pressure from the United States (US) and Western allies to release Taylor for trial at the Special Court for Sierra Leone (SCSL). Using desktop review, the findings showed that the asylum was an outcome of a multilateral agreement in which the United Nations (UN), African Union, Economic Community of West African States (ECOWAS), the US, and the United Kingdom (UK) played active roles. The paper also establishes that granting asylum to Taylor was within Nigeria’s international obligation under Article 12(3) of the African Charter on Human and Peoples’ Rights of 1981, for which Taylor qualified at the time of the asylum. Similarly, the Declaration of Territorial Asylum, 1967 gives asylum granting the state the powers to evaluate the grounds for granting such asylum. Thus, Nigeria’s asylum accorded to Taylor was the country’s prerogative and consistent with international law even though he was indicted for war crimes and crimes against humanity by the SCSL. Therefore, Nigeria’s action in granting asylum to Mr. Taylor neither violated any treaty to which Nigeria was a signatory at the time of granting the asylum nor amounted to a diplomatic blunder. Rather, Nigeria’s willingness to grant asylum to Taylor which subsequently led to the successful resolution of the Liberian crisis was widely commended in global diplomatic circles. Apart from applying indigenous diplomacy in conflict resolution, Nigeria’s rating as an effective regional power increased. To sustain the country’s pedigree of diplomatic excellence in resolving the Liberian crisis, Nigeria should rally ECOWAS countries to deepen economic integration, achieve self-reliance and make the sub-region less vulnerable to manipulation by Western powers.